Book Review: - Hans Thulesius (Grounded Theory Review: An International Journal)
This book on writing grounded theory is intended for the empirical GT researcher who wants to pursue his/her research until publication. It is the first book devoted entirely to such a crucial issue as writing grounded theory. Thus, Stop, Write: Writing Grounded Theory, is a practical book that fills a gap in GT methodology. In the first chapter of the book, Dr. Glaser says, “Stop unending conceptualization, unending data coverage, and unending listening to others who would egg you on with additional data, ideas and/or requirements or simply wait too long”. The book teaches the reader how to actually write a grounded theory by “simply” writing up the sorted memos. This requires efficient sorting that is dealt with in chapter two on Sorting Memos, which includes precious repetition from Theoretical Sensitivity (1978). How writing can be done effectively is outlined in chapter three, The Working Paper. Then follows chapter four on how to rework the first draft with the different tasks of editing for language and professionalism.